CMOS-Based High-Density Silicon Microprobe Arrays for Electronic Depth Control in Intracortical Neural Recording-Characterization and Application - Seidl, K.; Schwaerzle, M.; Ulbert, I.; Neves, H. P.; Paul, O.; Ruther, P. (Journal of microelectromechanical systems, 2012)
This paper reports on the characterization and intracortical recording performance of high-density complementary-metal-oxide-semiconductor (CMOS)-based silicon microprobe arrays. They comprise multiplexing units integrated on the probe shafts being part of the signal transmission path. Their electrical characterization reveals a negligible contribution on the electrode impedances of 139 ±11 kΩ and 1.2 ±0.1 MΩ and on the crosstalks of 0.12% and 0.98% for iridium oxide ( IrO x ) and platinum (Pt) electrodes, respectively. The power consumption of the single-shaft probe was found to be 57.5 μW during electrode selection. The noise voltage of the switches was determined to be 5.6 nV/√Hz; it does not measurably affect the probe performance. The recording selectivity of the electrode array is demonstrated by electrical potential measurements in saline solution while injecting a stimulating current using an external probe. In-vivo recordings in anesthetized rats using all 188 electrodes with a pitch of 40.7 μm are presented and analyzed in terms of single neural activity and signal-to-noise ratio. The concept of electronic depth control is proven by performing mechanical translation of the probe shaft while electronically switching to adjacent electrodes to compensate the mechanical shift.